2003
DOI: 10.1023/a:1022547110714
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The Kerr effect on vesicle-likedroplets (vesicles, cells or emulsion droplets) is described. Wegive a derivation of the Kerr constant for a dielectric fluiddroplet immersed in another fluid, assuming that the droplet in aweak electric field becomes a prolate ellipsoid. The Kerr constantis evaluated also for a droplet covered by a membrane of nonzerothickness. Comparing the theory with the experiment on dropletmicroemulsions from the literature, the bending rigidity constantof the surface layer is estimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…[22][23][24] On the other hand, only a few studies addressed the rheological behaviour of a single surfactant MLV. From the theoretical point of view, an (effective) MLV surface tension s eff was derived based on the small deformation theory 25,26 in analogy with sheared emulsion droplets or elastic capsules. 27 More recently, 28 we showed that MLVs of a well-known surfactant (linear alkylbenzenesulfonic acid, HLAS) deform at a constant volume under ow with different dynamic behaviours, i.e., tumbling (TU), breathing (BR) and tank-treading (TT), which are also found in unilamellar vesicles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24] On the other hand, only a few studies addressed the rheological behaviour of a single surfactant MLV. From the theoretical point of view, an (effective) MLV surface tension s eff was derived based on the small deformation theory 25,26 in analogy with sheared emulsion droplets or elastic capsules. 27 More recently, 28 we showed that MLVs of a well-known surfactant (linear alkylbenzenesulfonic acid, HLAS) deform at a constant volume under ow with different dynamic behaviours, i.e., tumbling (TU), breathing (BR) and tank-treading (TT), which are also found in unilamellar vesicles.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we carried out a scaling analysis based on the denition of a capillary number in analogy with emulsion droplets 32 and thus obtained a value of s eff for the system investigated in good agreement with theoretical predictions. 25,26 It should be pointed out that unilamellar vesicles have zero interfacial tension and their rheological behaviour can be well described in terms of a bending modulus only.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical processes at microdroplet-modified electrodes immersed in an aqueous solution present an interesting modeling challenge, which yields important insights into a plethora of chemical and biochemical phenomena. The majority of studies of oil microdroplets in the past have focused on the oxidation of N , N , N ‘, N ‘-tetraalkyl- para -phenylenediamines (TAPDs), partially due to their readily discernible redox moiety and their hydrophobic character given by long n -alkyl chains attached to the main redox body. To maintain electroneutrality within the microdroplets, upon oxidation of the TAPD to the radical cation TAPD +• , anion uptake from, or cation expulsion into the aqueous solution takes place. In particular, Schröder et al showed that the potential of insertion of these ions is controlled by the Gibbs energy of transfer of the electrolyte anion .…”
Section: Introductionmentioning
confidence: 99%
“…Another characteristic of a therapeutic community is clients' participitation in the management and decision-making in the community, through which they learn to function within day-to-day mutual human relationships (De Leon and Unterrainer, 2020). Clients jointly decide whether to allow other clients to move on to later phases of treatment (Kalina, 2008;Richterová-Těmínová et al, 2003). Another typical feature is the location, which is usually a small community or an isolated area where the clients are unable to obtain drugs (Therapeutic community for drug addicts, 2004).…”
Section: Theoretical Basesmentioning
confidence: 99%
“…The most important of these are called cardinal rules, which ensure the basic safety of the community's clients and are the only ones that are non-negotiable (Preslová et al, 2011). Violation of these rules can result in the expulsion of a client from the therapeutic community (Kalina, 2008;Richterová-Těmínová et al, 2003). Among the cardinal rules are prohibitions surrounding the use of drugs and alcohol, violence, discrimination, and normally, entering into intimate relationships with other clients (unless the community has given its consent to that).…”
Section: Kontakt / Journal Of Nursing and Social Sciences Related To ...mentioning
confidence: 99%